USE OF VIBRATORY STIMULATION IN THE REDUCTION OF SPASTICITY IN PATIENTS AFTER CEREBROVASCULAR ACCIDENT: LITERATURE REVIEW. (Fiep Bulletin - online, 2016)
INTRODUCTION: The vibratory stimulation is a rehabilitation technique that promotes the activation of the  somatosensory system through segmentary vibration or vibration on the entire body. The oscillatory waves generated by the vibration applied on patient are caught by peripheral receivers, they cause movement illusion and lead to the neural plasticity. Objective: to verify the effect of the vibratory stimulation in the spasticity modulation in patients after CVA. Method: bibliographical review of  scientific articles, published from 2010 to 2015 in the SCIELO and BIREME databases were used. Results: 7735 articles that appoached the subject were found, 08 of them fitted the inclusion criteria. Conclusion: The vibration stimulus are effective, because the vibration's mechanic action produces fast and small changes in the length of the tendon-muscle complex; it generates movement illusions and body changes; it improves the muscle strenght; it facilitates the voluntary movement and it reduces the spasticity.
Keywords: “spasticity”; “rehabilitation”; “cerebrovascular accident”; “vibratory/vibration”.